Digital Health Literacy – results of a representative survey among adults in Germany. (20th October 2021) - Zeeb, H; Pohlabeln, H; Preising, A; Schulz, B; Naczinsky, A; Dortmann, O; Kolpatzik, K
Abstract: : Whereas the concept of health literacy has already found its place in Public Health, this is less the case for digital health literacy (DiHL). To investigate the distribution of digital health literacy in the German adult population, we used a definition encompassing individual, social and technical competencies and resources to search, find, understand, apply and evaluate digital health information. We conducted a representative survey including 8.500 persons aged 18-75 years, based on an online access panel. All participants filled a questionnaire which covered the seven domains of the Digital Health Literacy Instrument (DHLI). Demographic information for participants was available through existing panel data. Optimal cut points to categorize digital health literacy were developed via regression modelling. Data were analysed using descriptive statistics and logistic regression modelling, comparing the two lower categories of DIHL against high/very high DiHL. Results are presented via odds ratios and 95% confidence intervals. Overall, 52.4% of respondents were categorized as having low or moderate DiHL (W: 51.2%; M: 53.7%). There were few differences according to age group and migration status. Those with higher educational attainment also scored higher in terms of DiHL. Operative competencies were generally rated high, whereas the evaluation of reliability of content scored lowest. In the regression analysis, the adjusted odds ratio (OR) for limited DiHL was 2.01 (95%CI 1.51;2.67) among those with poor or very poor self-reported health. Digital health literacy addresses a complex set of competencies and resources. More than half of the adult German population report a limited digital health literacy according to this nationwide survey. Impaired health is associated with low digital health literacy, and many have difficulties assessing the reliability of digital content. This is troublesome as more and more health-related information becomes digitalized. Key messages: More than half of the German adult population reports limited digital health literacy. Poor health status was found to be associated with low digital health literacy.